2007
DOI: 10.1038/sj.mt.6300201
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Clinical Manifestations of Canine Mucopolysaccharidosis I with Neonatal Retroviral Vector Gene Therapy

Abstract: Mucopolysaccharidosis I (MPS I) (Hurler syndrome) is due to deficient alpha-L-iduronidase (IDUA) activity and is the most common of the MPS disorders. Neonatal MPS I dogs were injected intravenously (IV) with a gamma retroviral vector containing a complete long-terminal repeat (LTR) and an internal human alpha(1)-antitrypsin (hAAT) promoter upstream of the canine IDUA complementary DNA (cDNA). This resulted in stable serum IDUA activity of 366 +/- 344 units (U)/ml (28-fold normal) for up to 1.8 years, which li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 40 publications
3
115
0
Order By: Relevance
“…Although pathological data were not available, progressive fragmentation of the elastic fibers likely contributed to worsening aortic valve function. In addition, gene therapy in mice [7] and dogs [5] only fully reduced aortic elastin fragmentation if serum IDUA activity was very high. The dense structure of the aorta likely reduces diffusion of enzyme, which may explain why the middle region is most refractory to treatment after gene therapy [5,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pathological data were not available, progressive fragmentation of the elastic fibers likely contributed to worsening aortic valve function. In addition, gene therapy in mice [7] and dogs [5] only fully reduced aortic elastin fragmentation if serum IDUA activity was very high. The dense structure of the aorta likely reduces diffusion of enzyme, which may explain why the middle region is most refractory to treatment after gene therapy [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…The severe (Hurler syndrome), intermediate (Hurler-Scheie syndrome), and mild (Scheie syndrome) forms of MPS I can all result in fragmented elastin fibers in the ascending aorta and cardiac valves in humans [2,3], which can result in aortic insufficiency due to reduced structural integrity of the valve. Dog [4,5] and mouse [3,6,7] models of MPS I also have elastin fragmentation of the ascending aorta and heart valves, which can result in aortic dilatation in addition to aortic insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Common therapeutic strategies include suicide gene therapy, oncolytic treatment, immunomodultion, gene replacement, proapoptotic treatment, and antiangiogenesis 175, 203. Successful delivery or efficacy of gene therapy approaches using viral vectors and plasmid DNA has been shown experimentally in canine brain tumor cells and brain using adenoviral,204, 205, 206, 207, 208, 209 retroviral201, 202, 210 herpes,211 and adeno‐associated viral212, 213, 214 delivery. Few viral therapies have progressed to phase III clinical trials, and none have been shown to have significant efficacy in high‐grade brain tumors in phase III trials to date 175…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Systemic intravenous delivery of an RV encoding the canine a-l-iduronidase (cIDUA) gene driven by a liver-specific promoter resulted in sustained, high levels of serum cIDUA with significant storage reduction and correction of cardiac function, vision, and bone mass density in the MPS I mouse model (Liu et al, 2005). However, in the MPS I dog, the same strategy resulted in 25% of the serum cIDUA levels seen in mice and only moderate clinical improvement (Traas et al, 2007). And in the MPS I cat, whereas cIDUA expression was similar to that seen in dogs, expression was transient because of a robust cytotoxic T lymphocyte response against cIDUAexpressing cells (Ellinwood et al, 2004;Ponder et al, 2006).…”
Section: Retroviral Vectorsmentioning
confidence: 99%